Influência da obesidade na recuperação autonômica cardíaca após exercício físico de moderada intensidade em jovens adultos - Barros, Mohana Epaminondas (2021)
Obesity can trigger cardiac autonomic dysfunction, in which there is a reduction in parasympathetic activity and/or an increase in sympathetic activity at rest and/or mental and physical stress conditions, exposing a greater risk of cardiovascular events. However, it is unclear whether obesity can affect cardiac autonomic recovery from a single bout of continuous moderate-intensity exercise. Objective: To verify whether obesity influences the behavior of heart rate variability and the time to complete vagal reactivation after a single session of moderate-intensity exercise. Method: 25 male individuals with 22.58 ± 2.05 years of age, irregularly active, well-nourished (n=14) and with grade I obesity (n=11) who underwent a period of rest, continuous moderate exercise session, participated in this study. intensity (ECMI: 30 min at 50-60% of heart rate reserve - HRres) and recovery period of 120 minutes. Cardiac autonomic control was analyzed by analyzing heart rate variability (HRV) throughout the experimental protocol. The HRV indices in the time (RMSSD, SDNN, pNN50%) and frequency (LF, HF, LF:HF) domains were obtained. Results: Significant differences were observed in the recovery period compared to rest in HR and in HRV indices in the obese group compared to normal weight peers. And the time to complete vagal reactivation analyzed from the RMSSD index was longer in those with obesity. Conclusion: Individuals with obesity present delay in the complete vagal reactivation of a continuous exercise session of moderate intensity.